Gender Inequality in Latin America - Berniell, María Inés (2024)
This paper examines gender inequality focusing on two critical spheres in which gender inequality is generated: education and work. Our objective is to provide a snapshot of gender inequality across key indicators as well as a dynamic perspective that highlights successes and failures. We also facilitate a cross-country comparison by grouping countries within Latin America by their level of economic development and drawing comparisons with countries outside the region. Finally, we reflect on differences in the ways that gender inequalities play out across different socio-economic groups, particularly those that highlight other sources of inequality.